1994
DOI: 10.1099/00207713-44-4-743
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Borrelia burgdorfeii Sensu Lato Evidenced by Restriction Fragment Length Polymorphism of rrf (5S)-rrl (23S) Intergenic Spacer Amplicons

Abstract: The organization of the ribosomal genes is unique in Borrelia burgdogeri in that the rrl (23s) and rrf (5s) genes are tandemly duplicated. We took advantage of this uniqueness to assess the restriction polymorphism of PCR products obtained with primers at the 3' end of the first rrfgene and at the 5' end of the second rrl gene. An amplicon that was 226 to 266 bp long was generated from 99 of 100 B. burgdorferi sensu lato strains. The nuclease MseI restriction polymorphism of the amplicons provided a useful too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
517
5
10

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(558 citation statements)
references
References 31 publications
26
517
5
10
Order By: Relevance
“…The isolates analysed were as follows: B. afzelii R-IP3, B. garinii 20047 and G2, B. andersonii 19857, B. japonica HO14 and IKA2, as well as isolates DN127, CA55, 25015 (see Casjens et al, 1995 for references for these nine isolates); PotiB1 and VS116 (Postic et al, 1994);and M63 (Nohlmans et al, 1995). These isolates typify the four named and five unnamed non-burgdorferi (sensu stricto) Lyme ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 581-596 Fig.…”
Section: Figmentioning
confidence: 99%
“…The isolates analysed were as follows: B. afzelii R-IP3, B. garinii 20047 and G2, B. andersonii 19857, B. japonica HO14 and IKA2, as well as isolates DN127, CA55, 25015 (see Casjens et al, 1995 for references for these nine isolates); PotiB1 and VS116 (Postic et al, 1994);and M63 (Nohlmans et al, 1995). These isolates typify the four named and five unnamed non-burgdorferi (sensu stricto) Lyme ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 581-596 Fig.…”
Section: Figmentioning
confidence: 99%
“…Previous studies suggested that this locus is not suitable for analysis of the molecular phylogeny of B. burgdorferi s.l. (De Michelis et al 2000;Postic et al 1994). In order to characterize and classify Borrelia burgdorferi s.l.…”
Section: Introductionmentioning
confidence: 99%
“…(20,35,54,56,57,61). The last decade of the 20th century brought a significant increase in the number of identified Borrelia strains in the United States (1,5,34,37,51,66). During 1992 to 1993, isolation of four unassigned American Borrelia sp.…”
mentioning
confidence: 99%
“…During 1992 to 1993, isolation of four unassigned American Borrelia sp. strains in California from I. pacificus and I. spinipalpis were reported (51,60,65). In 2007, the MLSA analysis of these strains confirmed their clustering into two groups distant from any other known species.…”
mentioning
confidence: 99%